Kepemimpinan dalam Perjanjian Baru: Konsep Kepemimpinan dalam Pelayanan dan Tulisan Paulus - Leonardus Rudolf Siby; Jane Lestari Darinding; Merline Mesti Kukus (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT. This paper presents Paul's leadership in ministry and Paul's writings as the hope of becoming a goal or starting point for Christian leaders in the church or in various institutions. The methodology or approach used in this paper uses a library method or approach, while data collection is carried out by reviewing and exploring several books or other information deemed relevant to the study. The finding in this study is to look at the basic principles of leadership According to Paul, servant leadership, leadership is self-presentation, a source of leadership authority, so that the attitude of the leader and the requirements to be a leader can create leaders with Christian characteristics who make Christ an example and role model.